A Descriptive Case Study of Skilled Football Goalkeepers During 1 v 1 Dyads: A Case for Adaptive Variability in the Quiet Eye - Franks, Benjamin; Roberts, William M.; Jakeman, John; Swain, Jonathan; Davids, Keith (Frontiers in Psychology, 2022)
Evidence investigating skilled performers in sport suggests that a prominent component of skilled behaviour is, in part, due to the development of more effective and efficient perception-action couplings. Further, the Quiet Eye has emerged as a useful tool in which to investigate how skilled performers regulate action through fixating on visual information within the immediate environment before the onset of a goal directed movement. However, only a few contributions to the literature have attempted to examine the individual variations within these Quiet Eye fixations in skilled participants. In this case study, we first asked how goalkeepers control their actions, via the Quiet Eye in a representative task. Second, we sought to examine whether inter- and intra- individual differences in the Quiet Eye are present in skilled goalkeepers as a functional component of skilled performance. Results were consistent with previous work on football goalkeepers, with QE fixations located at the ball and visual pivot. However, individual analysis reveals different Quiet Eye gaze patterning between (inter) and within (intra) the goalkeepers during saving actions. To conclude, we have provided a descriptive case study in attempt to understand the Quiet Eye behaviours of a skilled sample of professional goalkeepers. In doing so we have suggested how adaptive variability, founded upon an Ecological Dynamics framework, may provide further insight into the function of the Quiet Eye.